Case report: Complete atrio-ventricular block successfully reversed in newly diagnosed primary cardiac B-cell lymphoma - Mao, Jiahui; Xu, Yitong; Zhu, Mingfang; Wang, Luqun; Hou, Yu (Frontiers in Medicine, 2023)
Primary cardiac tumors are extremely uncommon and primary cardiac lymphoma (PCL) is an even rarer subset. A definite diagnosis can be delayed, which increases the likelihood of a poor prognosis. We report a case involving a 64-year-old male who presented with dyspnea, palpitation, and third-degree atrioventricular block (AVB) secondary to primary cardiac B-cell lymphoma that was diagnosed via endomyocardial biopsy (EMB) and multimodality imaging. Chemotherapy was initiated using rituximab, cyclophosphamide, vindesine, and prednisone (R-COP) followed by implantation of an artificial capsule pacemaker. Third-degree AVB vanished, and the subsequent cycle of treatment was adjusted as R-CDOP (rituximab, cyclophosphamide, doxorubicin liposome, vindesine, and prednisone), with aspirin and rosavastatin to prevent ischemic events. So far, the patient had a good clinical course and normal electrocardiogram. This case underscores the importance of EMB in the diagnosis of heart neoplasms. It is worth noting that anthracycline is not contraindicated in PCL.